KONFORMITAS TEMAN SEBAYA SISWA DITINJAU DARI JENIS KELAMIN - Mei Lani, Vini; Hariko, Rezki (Penerbit Lafadz Jaya, 2025)
This study aims to describe the level of peer conformity, as well as to determine the differences in peer conformity between male and female students at SMPN 1 Benai. The research method used is a quantitative method with a comparative research type. The sample in this study amounted to 142 with 71 male students and 71 female students. The sampling technique in this study was proportional random sampling. The data collection technique was carried out using a closed questionnaire. The data analysis technique used was the independent sample t-test. The results of the study showed that there were differences in peer conformity between male and female students with a significance value of p = 0.000 which is smaller than 0.05. When viewed from the average, female students had a higher level of conformity (mean = 99.51) than male students (mean = 93.49). This finding is important because it shows that differences in the level of conformity can affect how students adjust to group norms, both in aspects of behavior, attitudes, and beliefs. This research provides insights for educators and guidance and counseling teachers to design guidance and counseling services that can direct student conformity in a positive direction, thereby supporting personal and social development in the school environment.